Cutaneous metastasis: Indicators of internal malignancy diagnosed on fine needle aspiration cytology - Dr. Sujata S Giriyan; Dr. Rajesh H Chandan; Dr. Akanksha Agrawal (Tropical Journal of Pathology and Microbiology, 2018)
Introduction: Cutaneous metastases (CM) from various malignancies are uncommon with incidence of 0.8-4% and indicate disseminated disease with poor outcome. Metastatic adenocarcinoma to the skin occurs from gastro-intestinal tract, breast, lung and ovary and can be determined by high index of suspicion.Fine needle aspiration cytology is commonly employed for its diagnosis. CM from breast carcinoma to the chest wall are not very rare; however, distant CM are far less common occurring mostly within five years of its complete resection. Gastric adenocarcinoma presenting as CM is extremely rare, with 6%males and 1%females presenting likewise. Classically, these lesions appear as slow-growing, painless, discrete hard nodules with intact overlying epidermis.Case Report: We describe three cases of CM from malignancies of two organs & diagnosed on FNAC – 1) A 65 year male who underwent complete resection for breast carcinoma 10 years ago, presented with chest wall metastasis, 2) A 42 year female presented with distant CM following complete treatment for breast carcinoma 4 years ago, and 3) A 52 year female presented with CM nodules over abdomen after 3 years of radical gastrectomy and adjuvant chemotherapy.Conclusion: CM can be the first sign of disseminated malignancy; primary or post-surgery. CM can also occur in response to chemotherapy. Post-surgery, such skin lesions could occur as part of dissemination from another organ malignancy (dual malignancy).FNAC is a cost-effective, precise procedure for diagnosis of CM and also helps in differentiating these from various primary cutaneous malignancies and inflammatory conditions.